Polysaccharides based biopolymers for biomedical applications: A review - Jabeen, Nazish; Atif, Muhammad (Polymers for advanced technologies, 2024)
Polysaccharides are a class of natural biopolymers that have attracted significant attention due to their unique properties, which make them attractive for use in a wide range of applications. These biopolymers have an important role in our daily life, and designing biomaterials for biomedical applications requires careful consideration of factors such as biocompatibility, biodegradability, renewability, affordability, and availability, all of which can be achieved with polysaccharides. This review paper focuses on the use of polysaccharides in biomedical applications and provides an in‐depth analysis of the potential applications of arabinoxylan, a type of hemicellulose, in various fields, including drug delivery, infection control, tissue engineering, wound healing, and others. Arabinoxylan, which is derived from plants, is the most abundant and important class of hemicellulose and has a diverse role as a catalyst due to its biodegradability, biocompatibility, and renewable nature. Polysaccharide‐based biopolymers have applications in tissue engineering, wound covers, drug delivery systems, food preservation, and biocomposite films, making them an emerging excipient in pharmaceutical research. This review paper highlights the potential of polysaccharide‐based biopolymers in biomedical science and suggests that continued research and development will lead to broader and more innovative applications in the field. The use of polysaccharide‐based biopolymers has the potential to significantly advance healthcare and improve patient outcomes.